Neuroprotective Role of Omega-3 Fatty Acids: Fighting Alzheimer’s Disease - Mervin Chávez-Castillo; María Paula Gotera; Pablo Duran; María P. Díaz; Manuel Nava; Clímaco Cano; Edgar Díaz-Camargo; Gabriel Cano; Raquel Cano; Diego Rivera-Porras; Valmore Bermúdez (Molecules)
Alzheimer’s disease (AD) is one of the main causes of dementia, with an exponential increment in its incidence as years go by. However, since pathophysiological mechanisms are complex and multifactorial, therapeutic strategies remain inconclusive and only provide symptomatic relief to patients. In order to solve this problem, new strategies have been investigated over recent years for AD treatment. This field has been reborn due to epidemiological and preclinical findings that demonstrate the fact that omega-3 polyunsaturated fatty acids (ω-3 PUFAs) can be promising therapeutic agents because of their anti-inflammatory, antioxidant, and neurogenic-promoting activities, thus allowing us to classify these molecules as neuroprotectors. Similarly, ω-3 PUFAs perform important actions in the formation of characteristic AD lesions, amyloid-β plaques (Aβ) and neurofibrillary tangles, reducing the development of these structures. Altogether, the aforementioned actions hinder cognitive decline and possibly reduce AD development. In addition, ω-3 PUFAs modulate the inflammatory response by inhibiting the production of pro-inflammatory molecules and promoting the synthesis of specialised pro-resolving mediators. Consequently, the present review assesses the mechanisms by which ω-3 PUFAs can act as therapeutic molecules and the effectiveness of their use in patients. Clinical evidence so far has shown promising results on ω-3 PUFA effects, both in animal and epidemiological studies, but remains contradictory in clinical trials. More research on these molecules and their neuroprotective effects in AD is needed, as well as the establishment of future guidelines to obtain more reproducible results on this matter.